(untitled) (Research, Society and Development, 2020)
This article aims to evaluate the feelings involved with social isolation and its relationship with changes in eating habits and weight gain during the COVID-19 pandemic in Belo Horizonte and the metropolitan region. The methodology used was exploratory research of a quantitative nature. The questionnaire applied in June 2020 was prepared on Google Forms and obtained a sample of 700 respondents. The data were tabulated in Excel and analyzed in RStudio. The absolute and relative frequencies of the following variables were used: feelings perceived during social isolation, influence of isolation on people’s physical and mental health and change in eating habits. Subsequently, these data were used to cross-correlate these issues with weight variation. Of the 700 respondents, 83% were in social isolation during some time of the pandemic, and of these, 54% gained weight. Among the feelings involved with the pandemic, the highlights were anxiety, fear of relatives and friends becoming ill, uncertainty about the future and concern. Regarding the quality of food, 44% (p <0.0001) said they had worsened the quality of food consumption and 55% (p <0.0001) said they were eating more frequently. It was found that there was an increase in the consumption of sweets, soft drinks, alcohol, pasta and bakery items (p <0.0001).